THE APPLICATION OF KAHOOT PROGRAM IN TRIGONOMETRY LEARNING ENHANCEMENT ACTIVITY FOR MATHAYOM SUKSA 4 STUDENTS IN PRAMOCH WITTAYA RAMINTRA SCHOOL - อุ่นละม้าย พรรณี; บุญประจักษ์ เดช (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2018)
This research aimed to 1) compare Mathayom Suksa 4 students’ learning achievement in trigonometry after using the application of Kahoot program in trigonometry learning enhancement activity with the passing score of 70%; and 2) study Mathayom Suksa 4 students’ satisfaction towards using the application of Kahoot program in trigonometry learning enhancement activity. The sample group of this research consisted of 30 Mathayom Suksa 4 students in Pramoch Wittaya Ramintra School, selected one classroom out of all Mathayom Suksa 4 classrooms by using simple random sampling. The research instruments used for collecting data were 1) the application of Kahoot program in trigonometry learning enhancement activity for Mathayom Suksa 4 students, 2) a trigonometric achievement test for Mathayom Suksa 4 students, and 3) Mathayom Suksa 4 students’ satisfaction questionnaire in using the application of Kahoot program in trigonometry learning enhancement activity. The statistics used to analyze data were mean, standard deviation, and dependent sample t-test. The research results revealed that 1) Mathayom Suksa 4 students’ learning achievement after using the application of Kahoot program in trigonometry learning enhancement activity was higher than the passing score of 70% at the statistically significant level of .01; and 2) Mathayom Suksa 4 students’ satisfaction towards using the application of Kahoot program in trigonometry learning enhancement activity was at a high level.